Strategi Bisnis, Orientasi Pemasaran dan Kapabilitas Inovasi terhadap Keunggulan Bersaing Usaha Perikanan - Muhammad Sulton; Mokhtar Sayyid; Agustinus Agustinus; Permana Sufianto; Alifatus Sadiyah (Departement of Mathematics Education, 2023)
The fisheries, forestry and agriculture sectors could grow 2.15 percent year on year, in 2020. In the first quarter of 2021, this sector also grew 2.95 percent amidst the national economy which was still contracting 0.74 percent in gross domestic product (GDP) Nationally in 2020, the contribution of this fisheries subsector reached 3.7 percent. The combination of agriculture, forestry and fisheries contributed 14.5 percent to GDP in 2020, the second largest after the processing industry sector which contributed 19.8 percent. The Lamongan Regency Government in the 2020 fiscal year only spent IDR 1.9 billion to stimulate the fisheries sector, both fishing and cultivation. The research method used is research using quantitative methods. The survey was carried out by distributing questionnaires to respondents whose criteria had been determined, namely fishery business owners in Lamongan Regency. With a population, the number of cultivation business actors in Lamongan Regency in 2021 is 27,788 (Lamongan Regency Fisheries Service). The method was carried out by studying the extent of the influence of structural equation modeling or SEM, which is used to influence the competitive advantage of fisheries businesses in Lamongan Regency. This research specifically aims to investigate the factors that increase competitive advantage in Lamongan Regency, especially fisheries businesses.